Hybrid C18-Bonded Silica Phases: Application in Acetaminophen Adsorption - Carolina Feier Pinto; Fernando Silveira; Fernanda C. Stedile; João Henrique Z. dos Santos (Adsorption Science & Technology)
Hybrid silicas bearing octadecylsilane ligands and Lewis acid centres were synthesized by grafting and sol-gel methods. In grafting, Cp 2 ZrCl 2 was employed, while ZrCl 4 was used in the sol-gel method. A very low grafted metal content (ca. 0.1 wt% Zr/SiO 2 ) was achieved, with the carbon percentage being dependent on the grafting time. However, a much higher Zr content (up to 20.5 wt% Zr/SiO 2 ) and carbon content (up to 49.3%) was obtained by the sol-gel method. The surface concentration of alkyl groups varied between 0.2 and 2.8 μmol/m 2 . The solids were characterized by infrared spectroscopy (IR), ultraviolet diffuse reflectance spectroscopy (DRS), atomic force microscopy (AFM), scanning electron microscopy (SEM) and nitrogen adsorption. The behaviour of the phases towards the adsorption of acetaminophen was evaluated. Two phases showed a higher retention capacity than that exhibited by the commercial octadecyl phase. Recovery results remained between 70% and 100%.